Control of Fusarium wilt by wheat straw is associated with microbial network changes in watermelon rhizosphere - Lili Tang (Nature Portfolio, 2020)
Abstract Straw return is an effective strategy to alleviate soil-borne diseases. Though watermelon Fusarium wilt is a severe soil-borne disease, the effect of wheat straw on the disease remains unclear. Thus, we investigated the effects of wheat straw on soil bacterial and fungal communities by adding wheat straw to consecutive watermelon soil in the greenhouse condition. The microbiome changes were further investigated using network analysis based on 16S rDNA and internal transcribed spacer deep sequencing. Wheat straw addition increased the fungal community diversity, whereas the bacterial diversity was not affected. Compared to the control group, the relative abundance of some bacteria, including Actinobacteria, Chloroflexi, and Saccharibacteria, was increased with wheat straw addition. For fungi, the relative abundance of Fusarium was decreased with wheat straw addition. Microbial network analysis demonstrated that the fungal community has a more complex connection than the bacterial community. In addition, redundancy analysis indicated that the Fusarium genera were significantly related to the disease index. Taken together, the addition of wheat straw might affect the microbial community through increasing the relative abundance of phylum Actinobacteria, decreasing the relative abundance of Fusarium, and increasing the fungal network complexity to enhance the defense of watermelon against Fusarium wilt disease.